2007
DOI: 10.1111/j.1472-4642.2007.00355.x
|View full text |Cite
|
Sign up to set email alerts
|

Inferring historical introduction pathways with mitochondrial DNA: the case of introduced Argentine ants (Linepithema humile) into New Zealand

Abstract: The threat imposed by invasive species and difficulties associated with control and management places more impetus on trying to prevent their introduction. The identification of introduction pathways is a vital component towards this goal. In this study, we use a genetic marker‐based approach to retrospectively investigate the pathway of origin of the invasive Argentine ant (Linepithema humile) into New Zealand. We intensively sample the mitochondrial gene cytochrome b, from the entire known range of Argentine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 48 publications
3
61
0
Order By: Relevance
“…Consistent with this view, interception data suggest that while introductions from different primary sources commonly occur (e.g. Corin et al, 2007b), these must be only rarely successful given the relatively small number and large sizes of supercolonies in the introduced range (this study; see however Buczkowski et al, 2004;Sunamura et al, 2009a,b).…”
Section: The Origin and Development Of Introduced Supercoloniessupporting
confidence: 61%
See 1 more Smart Citation
“…Consistent with this view, interception data suggest that while introductions from different primary sources commonly occur (e.g. Corin et al, 2007b), these must be only rarely successful given the relatively small number and large sizes of supercolonies in the introduced range (this study; see however Buczkowski et al, 2004;Sunamura et al, 2009a,b).…”
Section: The Origin and Development Of Introduced Supercoloniessupporting
confidence: 61%
“…Furthermore, Sunamura et al (2009a) found that the European Main and the Californian supercolonies were both nonaggressive towards the large supercolony discovered in Japan (represented by Japan S2 in the present study). A detailed analysis of these six supercolonies based on the genetic diversity, the proportion of shared alleles and the Bayesian clustering methods implemented in Structure support the view of at least two secondary introductions events, one from Australia to New Zealand, as also suggested by Corin et al (2007b), and the other one from California to Hawaii. The geographic proximity of New Zealand to Australia and of Hawaii to California makes these introduction pathways plausible.…”
Section: Primary Introductions Of the Argentine Antmentioning
confidence: 99%
“…Applications have included tracking invasive species population sources (Corin et al 2007), wildlife forensics investigations (Dawnay et al 2007;Nelson et al 2007), ecology of cryptic communities (Corin et al 2007;Pfenninger et al 2007), and identification of prey from stomach contents (Pons 2006). Reliance on mitochondrial DNA in molecular taxonomy has been criticized because of numerous concerns ranging from introgressive hybridization and pseudogene ontogenesis to retention of ancestral polymorphisms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For such, an analysis of domain I sequences was performed on mtDNA samples from both, Brazil and part of the native range in Africa, to determine the dispersal pattern of the cattle egret in Brazil. Previous studies on other organisms involving mtDNA data have been successful in providing evidence to support well-informed conclusions regarding invasion dynamics (Corin et al 2007, Hoos et al 2010, Rollins et al 2011). The present study is based solely on results from the analysis of mtDNA, which is maternally inherited, and included a limited sample from the African continent.…”
Section: Discussionmentioning
confidence: 94%
“…Mitochondrial DNA (mtDNA) has been used in many studies on invasive species to identify historical introduction pathways or determine likely sources of introduced populations (e.g., Corin et al 2007, Hoos et al 2010. Rollins et al (2011) clarified the invasion pathways of the common starling (Sturnus vulgaris) in Western Australia based on mtDNA data.…”
Section: Introductionmentioning
confidence: 99%